Experimental study on jute-fiber-epoxy composite plate subjected to impact loading - Omar, Nurihan; Syed Mohamad, Sharifah Najwa; Aminanda, Yulfian; Syed Mohamed Ali, Jaffar; Kashif, Syed Muhammad (Trans Tech Publications, Switzerland, 2012)
World is currently focusing on alternate material sources that are environment friendly and biodegradable in nature. Due to the increasing environmental concerns, bio-composite made from natural fibers and polymeric resin, is one of the recent developments in the industry and constitute the present scope of experimental work. This work presents on advantages, mechanical and physical behavior of jute fiber – epoxy composites, one of the renewable alternatives. The biocomposite is experimentally investigated in term of low velocity impact loading. The experimental observations in term of damage mechanism, maximum force and maximum energy absorption were studied to understand the effect of fiber orientation. A comparative study with typical synthetic fibers like carbon and glass were also conducted.